Interference effect during word-task and colour-task in incongruent stroop-task - Hotama, Christianus Frederick; Nugroho, Hanung Adi; Soesanti, Indah; Oktoeberza, Widhia KZ (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2017)
Stroop-task is one of the most popular studies to check the ability of decision-making and cognitive process during high interference activity in the brain. In the incongruent Stroop-task, the difference between the colour that we read and the colour that we see produces high interference activities in the brain. This research aims to analyse the activity differences in each part of the brain during colour-task and word-task. This study investigates how well the ability of decision-making and cognitive process during high interference activities that occur in the brain. Electroencephalography (EEG) can record brain activities by recording the brain waves. The results show that recognising the colour is more difficult than that of the written words in the Stroop-task as indicated by statistical test with t-value greater than threshold value (t>2.0027) and significant level of 0.05. This study concludes that the colour-task gives more interference effect than the word-task. The more interference effect is produced, the more wrong decision-making is obtained.